ANALISIS FAKTOR KINERJA BIDAN TERHADAP PELAYANAN KEBIDANAN CONTINTY OF CARE DI TPMB - Fatmawati, Istiadah; Hidayati, Nurul (PRIMA WIYATA HEALTH, 2023)
Bacground: The concept of Continuity of Care is a service that covers the time from before pregnancy, pregnancy, delivery, and after delivery. The implementation of this service is related to the performance of a midwife. The performance of midwives can be influenced by internal factors, namely education, training, attitudes, motivation, length of service, knowledge and skills. There are 30 Midwife independent practice throughout Sidoarjo City that have made an MoU with PC IBI Sidoarjo City, but there are still midwives who have not provided Continuity of Care, one of which is due to the large influence of internal midwife factors. Purpose: The purpose of this study is to know the internal factors that affect the performance of midwives in providing Continuity of Care. Methods: This type of research is quantitative with the design of this study is "cross sectional". The population and sample of this study were all midwives who had Midwife independent practice who had MoU with PC IBI Sidoarjo City as many as 30 midwives with a sampling technique is total sampling. Types of data in this study are primary data, with unvariate data analysis, bivariate with Chi Square test, multivariate with Multiple Logistic Regression test. Results: The results of the data analysis showed that the majority with good performance were 18 people (60%), there was a significant effect between training and the performance of midwives p value (0.011.